2009
DOI: 10.1111/j.1365-3083.2008.02212.x
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to Yersinia pseudotuberculosis Infection is Linked to the Pattern of Macrophage Activation

Abstract: T helper 1 cells play a crucial role in the clearance of Yersinia pseudotuberculosis infection. By producing cytokines and presenting antigens to T cells, activated macrophages can orientate the adaptive immune response. The pathway used by macrophages to metabolize arginine has been employed as an important parameter to discriminate their activation state. In this study, the pattern of macrophage activation in Y. pseudotuberculosis-infected BALB ⁄ c (Yersinia-susceptible) and C57BL ⁄ 6 (Yersinia-resistant) mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Likewise, in the present study we found that YopP inhibited NO production and increased urea levels in a coordinate fashion with Gal1. In agreement with our findings, Silva Monnazzi et al and Tansini et al demonstrated that NO production in murine macrophages is suppressed by Y. pseudotuberculosis and that the YopP counterpart, YopJ, could be, at least in part, responsible of such effect [ 87 , 88 ]. In addition, we observed increased NO production by WT macrophages after inhibition of p38 and ERK1/2 signaling pathways and subsequent infection with Ye wt or Ye ∆ yopP .…”
Section: Discussionsupporting
confidence: 93%
“…Likewise, in the present study we found that YopP inhibited NO production and increased urea levels in a coordinate fashion with Gal1. In agreement with our findings, Silva Monnazzi et al and Tansini et al demonstrated that NO production in murine macrophages is suppressed by Y. pseudotuberculosis and that the YopP counterpart, YopJ, could be, at least in part, responsible of such effect [ 87 , 88 ]. In addition, we observed increased NO production by WT macrophages after inhibition of p38 and ERK1/2 signaling pathways and subsequent infection with Ye wt or Ye ∆ yopP .…”
Section: Discussionsupporting
confidence: 93%
“…LcrV-mediated IL-10 production also caused suppression of TNF-␣ production (39). Changes in IL-10 production have also been associated with Y. pseudotuberculosis infection in BALB/c mice (43). A recent publication has demonstrated that IL-10 production is a host response to systemic infection with Y. pestis (35).…”
Section: Discussionmentioning
confidence: 99%
“…The plates were incubated with L-arginine (100 µl) at 37°C for 30 min, and then H 2 SO 4 /H 3 PO 4 /H 2 O mixture (800 µl) was added and heated with α-isopropylidene nitrobenzene acetone (50 µl) at 95°C for 30 min. The complex in each well was diluted 20 times with PBS to detect the optical density (OD) values at 540 nm with a UV spectrophotometer [36], [37].…”
Section: Methodsmentioning
confidence: 99%